2015
DOI: 10.1038/onc.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

Cell growth density modulates cancer cell vascular invasion via Hippo pathway activity and CXCR2 signaling

Abstract: Metastasis of cancer cells involves multiple steps, including their dissociation from the primary tumor and invasion through the endothelial cell barrier to enter the circulation and finding their way to distant organ sites where they extravasate and establish metastatic lesions. Deficient contact inhibition is a hallmark of invasive cancer cells, yet surprisingly the vascular invasiveness of commonly studied cancer cell lines is regulated by the density at which cells are propagated in culture. Cells grown at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 57 publications
4
61
1
Order By: Relevance
“…We observed that cancer cells grown at low density present a highly invasiveness phenotype through upregulation of several cytokines including IL8, CXCL1, 2 and 3 as YAP appear to translocate to the nucleus. Inhibition of YAP-TEAD association using the inhibitor Verteporfin reversed this upregulation [7]. These findings matched with the YAP-dependent control of inflammatory cytokine expression and signaling in the mouse model of pancreatic cancer driven by mutant KRAS mentioned above [24].…”
Section: Special Report Sharif and Wellsteinsupporting
confidence: 73%
See 4 more Smart Citations
“…We observed that cancer cells grown at low density present a highly invasiveness phenotype through upregulation of several cytokines including IL8, CXCL1, 2 and 3 as YAP appear to translocate to the nucleus. Inhibition of YAP-TEAD association using the inhibitor Verteporfin reversed this upregulation [7]. These findings matched with the YAP-dependent control of inflammatory cytokine expression and signaling in the mouse model of pancreatic cancer driven by mutant KRAS mentioned above [24].…”
Section: Special Report Sharif and Wellsteinsupporting
confidence: 73%
“…The less compacted cells with nuclear YAP localization, give rise to the trophoectoderm while the more compacted cells in the inner cell mass show cytoplasmic localization of YAP [15,[30][31]. This is somewhat reminiscent of observations during malignant progression [7]: YAP cellular localization regulates the invasive capability of cancer cells and cancer cells forming lung metastases at the endothelial boundary of blood vessels showed nuclear YAP staining in contrast to cells distant from the endothelial invasion zone (Figure 2). Quite strikingly, signaling molecules involved in organ size control mechanisms coordinated by YAP also appear to contribute to invasive cancers [32][33][34].…”
Section: Special Report Sharif and Wellsteinmentioning
confidence: 83%
See 3 more Smart Citations